The Uneven Economic Diversification of Small and Mid-Sized Canadian Cities, 1971-2016 - Burnett, James; Brunelle, Cédric (Canadian Journal of Regional Science / Revue canadienne des sciences régionales, 2019)
Economic diversification is a long-standing public policy goal in Canada, driven by concerns about resource dependence and the need to remain innovative and competitive in a complex global economy. While considerable economic diversification of Canada’s urban regions has been noted by a range of observers, the phenomenon remains only partially understood. We propose to study the economic diversification process using an entropy decomposition approach, with industrial composition data compiled from census responses between 1971 and 2016 for 125 small and mid-sized urban regions. We demonstrate that, while industrial concentration indeed declines for almost all regions studied during the study period, trends are highly variable between regions. In about half of regions, diversification was mainly driven by job loss in goods-producing industries rather than job growth in new activities, whereas among the other half of regions, diversification was weaker, but job growth was stronger. This suggests a need for caution in interpreting changes in industrial concentration indices as evidence of economic success stories.